Cadmium toxicity on seed germination and initial growth of chia (Acta Scientiarum. Biological Sciences, 2019)
In recent years, there has been a growing concern related to soil and water contamination due to the constant dispersal of toxic metals. In addition to their ecotoxicological potential, these elements exhibit a cumulative character that favors their permanence in soil and passage to living organisms, which can lead to an ecological imbalance. Among toxic metals, cadmium (Cd) is an obstacle to agriculture because it can adversely affect food quality and human health, as well as diminish plant growth and productivity. Thus, the objective of this work was to evaluate the toxicity of cadmium on seed germination and initial growth of chia. The ecotoxicological effects of four Cd concentrations (15; 30; 45; and 60 mg L-1) were evaluated. The response variables were germination percentage, first count, germination speed index, total length, shoot length, root length, seedling dry mass, and tolerance index. It is concluded that the presence and accumulation of Cd in the culture substrate played an inhibitory role in seed germination and initial seedling growth of chia starting at 15 mg L-1. On the other hand, no significant effect was observed for the treatments in relation to dry mass of the chia seedlings.